2011
DOI: 10.5539/ijb.v3n3p52
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity and Phytochemical Analysis of Jatropha Curcas Plant against Some Selected Microorganisms

Abstract: Jatropha curcas is an ornamental plant which is also employed to cure various infections in traditional medicine. The hexane, ethanolic and aqueous extracts and latex of this plant were analysed phytochemically and screened against different microorganisms responsible for various human infections. Phytochemical analysis of the extracts and latex revealed the presence of many secondary metabolites including steroids, alkaloids and saponins. Ethanolic extract was found to be richer than hexane extract and aqueou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 7 publications
(6 reference statements)
4
33
1
2
Order By: Relevance
“…The plant parts have been used in traditional medicine to cure dysentery, gonorrhoea, infertility, small pox and skin infections (Akintayo 2004), while their insecticidal and antimicrobial properties have been proved by several reports (FagbenroBeyioku et al 1998;Georges et al 2008;Rahuman et al 2008;Arekemase et al 2011). The insecticidal potential of J. curcas leaf extract has been reported against larvae of Anopheles stephensi (Sakthivadivel and Daniel 2008), Aedes aegypti and Culex quinquefasciatus (Rahuman et al 2008;Sakthivadivel and Daniel 2008;Kovendan et al 2012).…”
Section: Introductionmentioning
confidence: 96%
“…The plant parts have been used in traditional medicine to cure dysentery, gonorrhoea, infertility, small pox and skin infections (Akintayo 2004), while their insecticidal and antimicrobial properties have been proved by several reports (FagbenroBeyioku et al 1998;Georges et al 2008;Rahuman et al 2008;Arekemase et al 2011). The insecticidal potential of J. curcas leaf extract has been reported against larvae of Anopheles stephensi (Sakthivadivel and Daniel 2008), Aedes aegypti and Culex quinquefasciatus (Rahuman et al 2008;Sakthivadivel and Daniel 2008;Kovendan et al 2012).…”
Section: Introductionmentioning
confidence: 96%
“…These findings are somewhat in contrast to the conclusions drawn by Arun et al, (2013) who inferred that neither the methanolic nor ethanolic extracts of the latex of J. curcas affected the growth of S. aureus. Arekemase et al, (2011) on the other hand, found extracts of J. curcas to be effective against both S. aureus and C.albicans. Clearly, the inhibitory effects of the plant extract are largely dependent on the concentration, parts of the plant used and the microorganisms involved (Kalimuthu et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Medicinal plants fit the criteria. Jatropha curcas, commonly known as physic nut, purging nut, Barbados nut or pig nut, has been used in traditional medicine for several generations to treat various health conditions including tumours, fever, jaundice, rheumatism, mouth infections and guinea worm sores (Rampadarath, 2016, Arekemase et al, 2011, Arun et al, 2013. Members of the rural communities of India have been known to use the herb in the treatment of dysentery and colic (Kalimuthu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The sterility of the extracts was determined according to the method of [22]. The respective extracts were inoculated on fresh sterile nutrient agar and incubated at 37°C for 24 h. The absence of growth after incubation is an indication of sterility.…”
Section: Sterility Of the Extractsmentioning
confidence: 99%